THE DIAGNOSTIC-ACCURACY OF DIGITAL RECTAL EXAMINATION, TRANSRECTAL ULTRASONOGRAPHY, PROSTATE-SPECIFIC ANTIGEN (PSA) AND PSA DENSITY IN PROSTATE CARCINOMA - (:unkn) unknown (WILEY, 1995)
Objective To evaluate the efficacy of digital rectal examination (DRE), transrectal ultrasonography (TRUS), prostate-specific antigen (PSA) and PSA density (PSAD) in the diagnosis of prostate cancer (CaP). Patients and methods Retrospective data were analysed from a selected population of 159 patients (mean age 66.7 years, range 50-83), 56 with histologically diagnosed CaP and 103 with benign prostatic hyperplasia (BPH). Results Among the four methods, DRE was found to have accuracy, sensitivity and specificity rates of 79.9, 91 and 73.8% respectively The most common clinical practice, the combination of PSA (>4 ng/mL), DRE and TRUS, showed a higher accuracy, a similar specificity rate, but a lower sensitivity (84.2, 91.2 and 71.4%, respectively). Rates from the combination of PSAD (>0.15 ng/mL/cm(3)) with DRE and TRUS were not significantly different from those obtained using the combination of PSA, DRE and TRUS. Conclusion PSAD alone or in combination did not improve the diagnostic Value of PSA. We cannot claim DRE was the best method for the diagnosis of CaP, because this study group did not represent a true screening population. However, this study revealed that DRE should not be omitted from the physical examination of patients and, despite technological developments, it remains a major tool in the diagnosis of CaP.
Keywords: DIGITAL RECTAL EXAMINATION; TRANSRECTAL ULTRASONOGRAPHY; PROSTATE SPECIFIC ANTIGEN; PROSTATE SPECIFIC ANTIGEN DENSITY AND PROSTATE CARCINOMA; CANCER; US